Effects of Synthesis Methods on the Physicochemical Properties of Micro- and Nano-Sized Zinc Oxide - Keshavarzi, Ashkan (2009)

(untitled)
Zinc oxide is an important semiconductor material, which is useful in various applications such as photo-electric devices electronic devices, surface acoustic wave, devices field emitters sensors, ultraviolet lasers and solar cells. With a wurtzite hexagonal phase, ZnO have a direct band gap of 3.37 eV with the larger exciton binding energy (60 meV), possesses a wide range of technological applications including flat panel displays, UV lasers and chemical and biological sensors. Till now, many methods have been developed to synthesize zinc oxide nanocrystals including vapor phase growth, ultrasonic irradiation, hydrothermal, pulsed lased deposition, vapor–liquid–solid process, soft chemical method, electrophoretic deposition, sol–gel process. Depending on the adopted synthesis method, zinc oxide nanocrystals would show various morphologies under different formation mechanisms.In this work, we studied preparation of ultra fine and nano sized ZnO by four important methods. ZnO nanoparticle, nanorod, nanowire have been successfully synthesized by facile methods like ultrasonic irradiation, sol-gel method, decomposition of Zn substrate and hydrothermal methods. In our work, three anionic surfactants Cetyl trimethylammonium bromide (CTAB), Tetrabutylammonium bromide (TBAB) and Sodium dodecyl sulfate (SDS) have been used as capping agent in the hydrothermal process. The results demonstrated that structure of the surfactant and its carbonyl chain group is important to crystal growth of the products. SEM and TEM micrograph revealed that nano fiber and ultrafine spherical ZnO prepared in the presence of CTAB and TBAB, but in the presence of SDS, sheet form of ZnO was prepared. The effect of ultrasonic irradiation was studied on preparation of ZnO. Nanoparticle of ZnO was synthesized after precipitation of zinc nitrate by urea at 90°C with irradiation of waves into the reaction flask for 2h. After heat treat at 350°C, sample was characterized with FT-IR, XRD, SEM, TEM and UV-vis. The results shows the nanoparticles of ZnO are in size range of 50-120nm. The effect of solvent was studied in this work, too. Ethanol, ethylene glycol and isopropanol were used as solvent in the reaction. In the other hand, characterization of products was shown that morphology and particle size of products was very different and depended to the dielectric constant of the solvents.